Prefrontal Physiomarkers of Anxiety and Depression in Parkinson’s Disease - de Hemptinne, Coralie; Chen, Witney; Racine, Caroline A.; Seritan, Andreea L.; Miller, Andrew M.; Yaroshinsky, Maria S.; Wang, Sarah S.; Gilron, Roee; Little, Simon; Bledsoe, Ian; San Luciano, Marta; Katz, Maya; et al. (Frontiers in Neuroscience, 2021)
Objective: Anxiety and depression are prominent nonmotor symptoms of Parkinson’s disease, but their pathophysiology remains unclear. We sought to understand their neurophysiological correlates from chronic invasive recordings of the prefrontal cortex. Methods: We studied four patients undergoing deep brain stimulation for their motor signs, who had comorbid mild to moderate anxiety and/or depressive symptoms. In addition to their basal ganglia leads, we placed a permanent prefrontal subdural 4-contact lead. These electrodes were attached to an investigational pulse generator with the capability to sense and store field potential signals, as well as deliver therapeutic neurostimulation. At regular intervals over 3-5 months, participants paired brief invasive neural recordings with self-ratings of symptoms related to depression and anxiety. Results: Mean age was 61  7 years, mean disease duration was 11  8 years and a mean UPDRS III off medication score of 37  13. Mean Beck Depression Inventory score was 14  5 and Beck Anxiety Index was 16.5  5). Prefrontal cortex spectral power in the beta band correlated with patient self-ratings of symptoms of depression and anxiety, with r-values between 0.31 and 0.48. Mood scores showed negative correlation with beta spectral power in lateral locations, and positive correlation with beta spectral power in a mesial recording location, consistent with the dichotomous organization of reward networks in prefrontal cortex. Interpretation: These findings suggest a physiological basis for anxiety and depression in PD, which may be useful in the development of neurostimulation paradigms for these nonmotor disease features.